PENGARUH PENGGUNAAN MEDIA WORD SEARCH PUZZLE TERHADAP KETERAMPILAN MEMBACA SISWA DI SANGGAR BELAJAR KAMPUNG BHARU MALAYSIA - Annisa; Syamsuyurnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using word search puzzle media on the skimming reading skills of fourth-grade students at Sanggar Belajar Kampung Bharu, Malaysia. The research employed a quasi-experimental method with a one group pretest–posttest design. The population consisted of 12 fourth-grade students. Data were collected through a skimming reading observation sheet that had been validated by a subject matter expert in Indonesian language education, and were analyzed using a paired sample t-test through SPSS 25.0. The results showed that the average score of students’ skimming reading skills was 52.50% in the pretest and 88% in the posttest. Based on the results of the hypothesis test, a significance value of 0.000 (<0.05) was obtained, indicating that the use of word search puzzle media has a significant effect on the skimming reading skills of fourth-grade students at Sanggar Belajar Kampung Bharu, Malaysia.